Impact of Educational Interventions on Knowledge About Hypertensive Disorders of Pregnancy Among Pregnant Women: A Systematic Review - Gholami, Kosar; Norouzkhani, Narges; Kargar, Meraj; Ghasemirad, Hamidreza; Ashtiani, Atieh Jafarabadi; Kiani, Shamim; Sajedi Far, Mahdi; Dianati, Maryam; Salimi, Yasaman; Khalaji, Amirmohammad; Honari, Sara; Deravi, Niloofar (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: Hypertensive disorders of pregnancy (HDP) including chronic hypertension, preeclampsia and gestational hypertension is the cause of about 50000 deaths out of 400000 perinatal deaths. HDP is an effective risk factor of stroke, type 2 diabetes and cardiovascular diseases like ischemic heart disease. There is a significant relation between HDP, lifestyle and knowledge. Unfortunately, many studies showed that pregnant women have lack of knowledge about HDP. Therefore, the importance of educational interventions is today, more acknowledged than before. Aim: The goal of this systematic review was to investigate the effect of interventional educations on the knowledge of pregnant women about HDP. Meth-ods: A systematic review of the related articles was conducted. We included English random-ized controlled trials published up to December 2021 including pregnant women as popula-tion, HDP as the outcome and educational interventions as the intervention. Results: After the process of study selection, six articles containing 819 pregnant women were included in this study. Educational pamphlet, mobile-based application, a mixture of pamphlet, picto-graphic magnet and videos and a combination of PowerPoint, data show projector and con-versation were the educational interventions in these studies. Conclusions: The positive ef-fects of educational interventions on the knowledge of women with HTP were observed in all studies. The higher knowledge leads to HDP-related complications.